PjBL Learning Training Based on Science Practicum Tools DNA and RNA Structures at the Attohiriyah Alfadiliyah Islamic Boarding School - Ahmad Aris Arifin; Aris Doyan; Mahrus Mahrus; Susilawati Susilawati; Yayuk Andayani; Muntari Muntari (Unram Journal of Community Service, 2023)
The demands of globalization and the change of educational paradigms, bringing new policies in the field of education in Indonesia, namely the application of the curriculum MBKM (Merdeka Learning Kampus Merdeka), with the main characteristic is project-based learning that aims to develop soft skills and build the character of student profile Pancasila on pupils. In addition, today's science learning is still faced with challenges and problems, which are caused by the lack of participation of students in the learning process, lack of motivation and interest of students to learn science, inadequacy of learning materials with the needs and environment of students, inappropriate learning methods, as well as non-variative and innovative learning resources such as lack of use of tools. Then to solve this problem one of the ways you can do is by giving training to make science gear. So, the purpose of this activity is to train the teacher in making science gear, especially related to the use of ice cream sticks used as the basic material for building media structures of DNA and RNA. This dedication activity has been carried out locally, located in the Pondok Pesantren Attohiriyah Alfadiliyah Bodak, Central Lombok. The implementation of service activities has been carried out well, through three stages, namely, preparation, implementation, to evaluation and reporting. This dedication activity has been carried out locally, located in the Pondok Pesantren Attohiriyah Alfadiliyah Bodak, Central Lombok. The implementation of service activities has been carried out well, through three stages, namely, preparation, implementation, to evaluation and reporting. This dedication activity has been carried out locally, located in the Pondok Pesantren Attohiriyah Alfadiliyah Bodak, Central Lombok. The implementation of service activities has been carried out well, through three stages, namely, preparation, implementation, to evaluation and reporting